2021
DOI: 10.3390/su13169400
|View full text |Cite
|
Sign up to set email alerts
|

Hydroponic Phytoremediation of Ni, Co, and Pb by Iris Sibirica L.

Abstract: Heavy metal pollution in mine wastelands is quite severe. Iris sibirica L., an emergent wetland plant, is characterized by an ability to survive under high stress of heavy metals. This study aimed to explore the phytoremediation ability of nickel (Ni), cobalt (Co), and lead (Pb) by Iris sibirica L. under hydroponic conditions. A series of tests were conducted at different metal stress conditions to evaluate the phytoextraction and tolerance of Iris sibirica L. The concentrations of Ni, Co, and Pb in plant shoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Helianthus annuus can simultaneously absorb As, Cd, Cr, nickel (Ni), and Fe, and a significant increase of the As and Cd enrichment phenomenon was observed [53]. Iris sibirica can tolerate and accumulate Pb, cobalt (Co), and Ni, and the bioaccumulation factor of Pb is greater than one, indicating that it has a good phytoremediation potential for Pb and can be used for the remediation of mineral wastewater [54]. Researchers also used sunflower to absorb and accumulate radioactive elements, Cd, plutonium (Pu) [55], uranium (U) [56], and radon-222 [57].…”
Section: Mechanism Of Hydroponic Plants To Purify Wastewatermentioning
confidence: 99%
“…Helianthus annuus can simultaneously absorb As, Cd, Cr, nickel (Ni), and Fe, and a significant increase of the As and Cd enrichment phenomenon was observed [53]. Iris sibirica can tolerate and accumulate Pb, cobalt (Co), and Ni, and the bioaccumulation factor of Pb is greater than one, indicating that it has a good phytoremediation potential for Pb and can be used for the remediation of mineral wastewater [54]. Researchers also used sunflower to absorb and accumulate radioactive elements, Cd, plutonium (Pu) [55], uranium (U) [56], and radon-222 [57].…”
Section: Mechanism Of Hydroponic Plants To Purify Wastewatermentioning
confidence: 99%
“…In addition, Iris wilsonii plants decreased after 60 days of an experimental hydroponic study under acid mine drainage which was indicated based on the decay of the roots of some plants(Wu et al, 2022). The concentration of Ni markedly caused serious toxicity symptoms of Iris sibirica L. Both the root and shoot biomass appeared erratic with the increasing concentrations of Ni and eventually, they died(Wan et al 2021). On the contrary,Caldelas et al (2012) reported high rate of surviving and continued growth of Iris pseudacorus L. plants in nutritive solution with ZnCl 2 , along with remarkable accumulation of Zn in roots and leaves.…”
mentioning
confidence: 99%